PENGEMBANGAN MEDIA PEMBELAJARAN BLOGPADA MATERI PENCEMARAN LINGKUNGAN UNTUK KELAS X - Fitroh Dwi Apriliawan Hariyoto (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2013)
Blog learning media on the material of enviromental pollution is expected to be used for increasing student learning motivation. The delight of student in accesing information from the internet along with the rapid technological developments can be used to create an internet-based media, one of them is blog, to attract the student’s interest in learning. Interisting display blogs that can be filled with pictures and videos to better motivate students to learn. This research includes the development of research in order to produce a viable media blog theoretically and empirically. Results showed media blog is theoretically feasible with percentages of 91.9% (categories: very feasible) and empirically with percentage 92.7% (categories: very feasible).Keywords: blog, learning media, enviromental pollution